Analysis of compressive properties of the BioAid hearing aid algorithm. (25th May 2018) - Clark, Nicholas R.; Lecluyse, Wendy; Jürgens, Tim
Abstract: Objective : This technical paper describes a biologically inspired hearing aid algorithm based on a computer model of the peripheral auditory system simulating basilar membrane compression, reflexive efferent feedback and its resulting properties. Design : Two evaluations were conducted on the core part of the algorithm, which is an instantaneous compression sandwiched between the attenuation and envelope extraction processes of a relatively slow feedback compressor. Study sample : The algorithm's input/output (I/O) function was analysed for different stationary (ambient) sound levels, and the algorithm's response to transient sinusoidal tone complexes was analysed and contrasted to that of a reference dynamic compressor. Results : The algorithm's emergent properties are: (1) the I/O function adapts to the average sound level such that processing is linear for levels close to the ambient sound level and (2) onsets of transient signals are marked across time and frequency. Conclusion : Adaptive linearisation and onset marking, as inherent compressive features of the algorithm, provide potentially beneficial features to hearing-impaired listeners with a relatively simple circuit. The algorithm offers a new, biological perspective on hearing aid amplification.